High-strength steel for hull structure as well as preparation process and application of high-strength steel

Through high-throughput calculation and CALPHAD thermodynamic method, screening the combination of suitable gold and preparing high-strength steel containing Heusler phase, the problem of limited strengthening effect of Cu-HSLA steel is solved, and the hull material with excellent strength and toughness is achieved, reducing the preparation cost and improving the mechanical properties.

CN119530677APending Publication Date: 2025-02-28WUHAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411644142.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The strengthening effect of existing Cu-HSLA steel is limited, the preparation cost is difficult to reduce, the mechanical properties are difficult to improve, and it is difficult to meet the material needs of next generation high-performance ships.

Method used

Using an ICM framework and CALPHAD thermodynamics method based on high-throughput calculations, suitable alloy combinations are screened, and high-strength steel containing Heusler phase is prepared by arc smelting and homogenization, simplifying the preparation process and reducing costs.

Benefits of technology

It significantly improves the strength and toughness of hull materials, shortens the preparation cycle, reduces production costs, and promotes the application of high-strength and tough steel materials in the next generation of ship structure design and transportation scale design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005139259150000011
    Figure HDA0005139259150000011
  • Figure HDA0005139259150000012
    Figure HDA0005139259150000012
  • Figure HDA0005139259150000021
    Figure HDA0005139259150000021
Patent Text Reader

Abstract

The invention discloses high-strength steel for a hull structure as well as a preparation process and application of the high-strength steel. The Cu-containing marine HSLA steel with high strength and excellent toughness is designed and manufactured by adopting a Fe-Si-Ti system through a Heusler phase precipitation strengthening theory, and the method comprises the following steps: firstly, screening hundreds of thousands of combinations in an HSLA-115 combination space, and determining a sample component S1 by using an ICM framework based on CALPHAD thermodynamics and high-throughput calculation; and then, accurately weighing high-purity elements, casting button ingots by using an electric arc melting furnace in vacuum and argon environments, re-melting to ensure that the components are uniform, and finally, carrying out homogenization treatment and aging treatment. A Heusler precipitated phase is generated in the prepared high-strength steel, so that the Cu-containing marine HSLA steel is effectively strengthened, the Cu-containing marine HSLA steel has the characteristics of high strength and high toughness, meanwhile, the preparation period is short, the cost is low, and conversion and application of the high-strength and high-toughness steel in the next-generation ship structure and transportation scale design are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of ship mechanical protection, and in particular relates to a high-strength steel for hull structure and a preparation process and application thereof. Background Art

[0002] The type and distribution of microstructure affect the strength and toughness of high-strength low-alloy steel (HSLA) for ships. The microstructure of ship steel mainly contains polygonal ferrite, austenite, low-carbon bainite and low-carbon martensite. For ferrite / austenite steel, compared with low-carbon bainite and low-carbon martensite, the formability is excellent, but the resistance of polygonal grain boundaries to low-temperature crack propagation is relatively weak. In addition, after the phase transformation of polygonal ferrite, large-sized medium-carbon islands will be formed, which will become the starting point of brittle fracture and curb the development of ship steel.

[0003] HSLA steels containing Cu are known for their good weldability, high strength and high and low temperature toughness. These properties, coupled with their lower cost, make them important in the design of structures such as ships and offshore platforms. Their low carbon content (i.e. <0.06wt.%) ensures a minimum carbon equivalent (CE) value, providing excellent resistance to hydrogen-induced cracking. The addition of Cu compensates for the loss of strength due to the reduction in C content, resulting in the simultaneous co-precipitation of Cu clusters and M2C (M: Mo, Cr and Fe) carbides during aging. In addition, the addition of Nb further improves toughness and leads to the formation of carbonitrides, which inhibits grain growth during austenitization.

[0004] Although extensive development and mechanical property research of HSLA steels containing Cu and M2C have been carried out, the strengthening effect of Cu-HSLA steel is still limited. The next generation of high-performance ships still face typical structural material problems of "difficulty in reducing preparation costs" and "difficulty in improving mechanical properties". Therefore, it is necessary to further study modification methods for commonly used Cu-containing marine steels to make them have the characteristics of high strength and high toughness, and meet the on-demand customization of new hull structural materials for ship design and performance requirements. Summary of the invention

[0005] In view of the typical structural material problems of "difficulty in reducing preparation costs" and "difficulty in improving mechanical properties" faced by the next generation of high-performance ships, the purpose of the present invention is to provide a high-strength steel for hull structure and its preparation process and application, and to introduce a modification method for high-strength steel containing Heusler phase based on high-throughput calculation for hull structure, which can significantly shorten the hull material preparation cycle, simplify the preparation process, reduce production costs, and promote the transformation and application of high-strength and toughness steel materials in the next generation of ship structure design and transportation scale design.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A preparation process for high-strength steel for hull structure is provided, comprising the following steps:

[0008] 1) Screening 100,000 combinations in the HSLA-115 combinatorial space, and using the selected research samples based on the ICM framework of CALPHAD thermodynamics, the Thermo-Calc software was used for high-throughput calculation to determine the sample composition. The specific composition by mass percentage is: 0.06% C, 88% Fe, 2.6% Al, 1.6% Si, 2.5% Ti, 0.8% Cr, 1% Mn, 0.6% Ni, 1.5% Cu, 0.54% Nb, 0.8% Mo;

[0009] 2) Based on the sample composition obtained in step 1), a balance with an accuracy of ±0.1 mg is selected to weigh the elemental substance, and an arc melting furnace is used to cast the sample in a vacuum, argon-filled atmosphere and a water-cooled copper mold. The cast sample is repeatedly remelted to ensure uniform chemical composition, and pure Zr is used to remove the remaining O2 in the casting chamber;

[0010] 3) homogenizing the sample obtained by casting in step 2) at 1190-1210° C. for 115-125 min, and then quenching with water;

[0011] 4) The sample after homogenization treatment in step 3) is subjected to aging treatment at 490-510° C., and finally water quenched to room temperature to obtain high-strength steel for hull structure.

[0012] According to the above scheme, the aging treatment process is: insulation treatment is carried out at a constant temperature of 500°C for 2, 4, 8 and 12 hours respectively.

[0013] According to the above scheme, in step 1), the Thermo-Calc software is used to perform a high-throughput calculation application programming interface toolkit, namely TC-Python with a TCFE9 steel database.

[0014] According to the above scheme, in step 2), the purity of the single element is high purity > 99.9wt.%.

[0015] According to the above scheme, in step 2), the cast sample is repeatedly remelted 5 to 7 times.

[0016] According to the above scheme, in step 4), TC-Prisma simulation is used to estimate the optimal range of failure time, and the main parameter is the interface free energy (γ), wherein regarding the precipitation behavior of Fe2SiTi phase in Fe-Si-Ti system, the constant value γ is set to 0.145 J / m in the aging simulation. 2 .

[0017] According to the above scheme, in step 4), the obtained high-strength steel for hull structure contains Heusler phase.

[0018] According to the above scheme, in step 4), the high-strength steel for hull structure obtained has a tensile strength of 840-870 MPa, an elongation of 17.5-22.5%, and a total impact absorption energy of 45.3-65.3 J in a Charpy V-notch test at -40°C.

[0019] Provided is a high-strength steel for hull structure prepared by the above method.

[0020] Provided is an application of the above-mentioned high-strength steel for hull structure in ship steel.

[0021] ICME (Integrated Computational Materials Engineering) tools can significantly accelerate the process of alloy development. In particular, the CALPHAD (phase diagram calculation) method can accurately predict the phase equilibrium of many traditional steels. For steels containing unconventional precipitates, the stability of the Heusler phase (intermetallic compound X2YZ) can be directly confirmed by thermodynamic studies. The present invention adopts the Fe-Si-Ti system to design and manufacture high-strength, high-toughness Cu-containing marine HSLA steel through the Heusler phase precipitation (especially Fe2SiTi Heusler phase) strengthening theory. Compared with other common precipitation phases, Fe2SiTi Heusler can precipitate at a higher volume percentage (~6vol.%), solving the challenges of high-performance ship materials in preparation cost and mechanical properties. First, 100,000 combinations are screened in the HSLA-115 combination space, and the sample composition S1 is determined using the ICM framework based on CALPHAD thermodynamics and high-throughput calculations. Then, high-purity elements are accurately weighed and button ingots are cast using an arc melting furnace in a vacuum and argon environment. The sample is remelted to ensure uniform composition, followed by homogenization and aging. The microstructure was observed through standard metallographic procedures, and it was found that the sample contained a large number of fine precipitates. Its tensile strength was 855±15MPa, elongation was 20±2.5%, and the total impact absorption energy of the -40℃ Charpy V-notch test was 55.3±10J.

[0022] The beneficial effects of the present invention are as follows:

[0023] 1. The present invention provides a preparation process for high-strength steel for hull structure. After high-throughput computational screening and post-heat treatment selection, Heusler precipitation phase is generated to effectively strengthen Cu-containing marine HSLA steel, which has the characteristics of high strength and high toughness. The process significantly shortens the preparation cycle of hull materials, simplifies the preparation process, reduces production costs, and promotes the transformation and application of high-strength and toughness steel materials in the next generation of ship structure design and transportation scale design.

[0024] 2. The present invention proposes a design method for the coordinated performance of strengthening / toughening / lightweighting levels of steel materials, and provides a design method for strengthening, toughening, and low-cost steel materials for hull structures, thereby realizing on-demand customization of new hull structural materials that meet ship design and performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a flow chart of a method for designing a steel material for strengthening and toughening a hull structure in an embodiment of the present invention.

[0026] Figure 2 In Example 1 of the present invention, the composition range of the alloy is obtained by high-throughput calculation: (a) S1; (b) S2.

[0027] Figure 3 Thermodynamic calculation of steel in Example 1 of the present invention: (a, b) the change of phase fraction with temperature; (c, d) the evolution process of phase structure with decreasing temperature.

[0028] Figure 4 The microstructures of the cast steel in Example 1 (S1) of the present invention and Comparative Example 1 (S2): (ac) S1; (df) S2.

[0029] Figure 5 The microstructures of the as-cast steel after homogenization at 1200° C. in Example 1 (S1) of the present invention and Comparative Example 1 (S2): (ac) S1; (df) S2.

[0030] Figure 6 The precipitation kinetics of the precipitated phase of Example 1 of the present invention at different temperatures and times: (a) different temperatures; (b) different times.

[0031] Figure 7 The precipitation states of the steel obtained in Example 1 of the present invention and Comparative Example 1 under different aging processes are as follows: (ad) S1; (eh) S2.

[0032] Figure 8 The hardness comparison of the steel obtained in Example 1 of the present invention and other commercial HSLA. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0034] Example 1

[0035] Provide a preparation process for high-strength steel for hull structure, the flow chart is as follows Figure 1 As shown, the following steps are included:

[0036] Step 1. After screening one hundred thousand combinations in the HSLA-115 combinatorial space, the research samples were selected using the ICM framework based on CALPHAD thermodynamics. The Thermo-Calc software was used for the high-throughput computational application programming interface (TC-API) toolkit, namely TC-Python with the TCFE9 steel database. The evolution of phase fraction and phase composition with temperature, as well as non-equilibrium Scheil-Gulliver solidification, were used to guide composition screening and the selection of homogenization and heat treatment temperatures. TC-Prisma simulations were used to estimate the optimal range of failure time, with the main parameter being the interfacial free energy (γ). Regarding the precipitation behavior of the Fe2SiTi phase in the Fe-Si-Ti system, the constant value γ = 0.145 J / m was set in the aging simulation. 2 The composition of sample S1 was finally determined to be 0.06C88Fe2.6Al1.6Si2.5Ti0.8Cr1Mn0.6Ni1.5Cu0.54Nb0.8Mo, and the precipitation phase was promoted by Nb and Mo.

[0037] Step 2: According to the designed composition, high purity elements (>99.9wt.%) were weighed using a high precision balance (accuracy ±0.1mg). 10g button ingots were cast for each designed composition using an arc melting furnace in a vacuum, argon-filled atmosphere and a water-cooled copper mold. The ingots were remelted six times to ensure uniform chemical composition, and pure Zr was used to remove the remaining O2 in the casting chamber.

[0038] Step 3: Cut a disc-shaped sample from the button ingot, encapsulate it in a vacuum quartz tube, and homogenize it at 1200°C for two hours according to the predicted results of the CALPHAD model, and then quench it with water.

[0039] Step 4: In order to evaluate the aging evolution behavior, according to the results predicted by the CALPHAD model, the samples were kept at a constant temperature of 500 °C for 2, 4, 8 and 12 hours, respectively, and water quenched to room temperature to produce high-strength steel containing Heusler phase.

[0040] The metallographic specimens were polished and etched with nitric acid solution according to the standard metallographic process. The microstructure was observed using JEOL JSM7800 FSEM. It was observed that the S1 sample contained a large number of fine precipitates.

[0041] The tensile results of the cast S1 containing the Heusler phase prepared in Example 1 showed a tensile strength of 855±15 MPa, an elongation of 20±2.5%, and a total impact absorption energy of 55.3±10 J in a Charpy V-notch test at -40°C.

[0042] Comparative Example 1

[0043] The classic HSLA sample S2 was selected for microstructure comparison, and the chemical composition was 0.06C88Fe2.6Al.6Si2.9Ti0.8CrMn1.5Ni1.5Cu0.02Nb0.02Mo. The preparation process was the same as that in Example 1.

[0044] By using JEOL JSM7800F SEM to observe the microstructure, although the comparative sample S2 also contains Cu element and has similar microstructural morphology, no high-density precipitated phase is found.

[0045] The tensile strength of the conventional cast S2 prepared in Comparative Example 1 is 538±13MPa, the elongation is ±3.2%, and the total impact absorption energy of the Charpy V-notch test of the specimen at -40°C is 27.0±3J.

[0046] The main design idea of ​​the Heusler phase in the steel of the present invention is to preserve:

[0047] By using the stable characteristics of the Laves phase at high temperatures and the control of the characteristics of Si and Nb elements, the limitations of the Fe2SiTi metastable state are broken. At 1200°C, the Fe2SiTi Heusler phase is preserved in sample S1, and Fe2SiTi and the black, elongated, irregular Laves Fe2Ti phase coexist at the grain boundaries. The Laves Fe2Ti phase has a high solubility range for Si at high temperatures (e.g., 27 at.%), thereby utilizing the mutual diffusion of Si in Fe2Ti to promote the formation of the Fe2SiTi phase.

[0048] The high Nb content of the Laves phase in the cast S1 sample indicates that Nb atoms can dissolve into the Ti sublattice to form a Fe2(Ti,Nb) structure, which is consistent with the size factor principle that controls the chemical properties of the Laves phase. The similar sizes of Ti and Nb and Fe2Ti and Fe2Nb are common variants of the Laves_C14 structure. Therefore, in addition to the thermodynamic affinity and grain boundary coexistence of Laves and Fe2SiTi, and the high solubility of Si in the Laves phase. The formation of the Nb-rich Heusler phase, which is designed to take into account the principle of differential Nb solubility, causes sufficient Si to diffuse into the Nb-rich Laves phase, so that the metastable Heusler phase can be preserved, depending on the physical properties of the elements and phase structure.

[0049] The synergistic strengthening effect and precipitation kinetics of the Heusler phase in the steel of the present invention are:

[0050] S1 has significant strengthening and toughening, breaking through the limitations of grain boundary cracking. The grain refinement and strengthening effect is achieved through the pinning of Fe2SiTi particles during the homogenization process. The average grain size after aging does not exceed 80μm, while the grain size of the S2 aged sample as a comparison sample is two to three times larger. The Heusler phase plays a Zener pinning role, resulting in the grain size of all four S1 samples with different aging times remaining relatively constant. This is because the volume percentage and average size of the blocky Fe2SiTi in the grain boundary are roughly constant. Especially after a long-term failure of 12h, there is no obvious coarsening of the Fe2SiTi at the grain boundary, and only a little dissolution, which proves that the Heusler phase is an effective grain refiner.

[0051] In addition, the coexistence of Fe2SiTi and Cu precipitates and the limited solubility of Al in these precipitates indicate that the Fe2SiTi phase has Nb solubility, playing the role of Nb in the Laves transformation and the formation of Nb-rich Fe2SiTi phase at higher temperatures. The volume percentage and size of both precipitates in S1 increased slightly, while their number density also decreased. Such a slow coarsening rate indicates that the Heusler phase is an effective strengthening precipitate in HALS steel.

[0052] There are qualitative differences in the microstructure of S1 and S2 after aging. The precipitates observed in S1 are finer and more abundant than in S2, which is an important reason for the significant difference in mechanical properties between the steels.

[0053] The first coherent Cu clusters formed are driven by higher positive mixing enthalpy and significant segregation tendency. For HSLA, Cu precipitates are formed after aging at 550°C for 0.12-0.25 hours. On the other hand, Fe2SiTi precipitates uniformly due to its coherence with the BCC matrix and small lattice mismatch. However, the Cu content increases near the Fe2SiTi precipitates, indicating that the Heusler phase can be formed simultaneously with the Cu precipitates. The coprecipitation of the two precipitates is more obvious in S1 than in S2, indicating that the volume percentage of Fe2SiTi in S1 is higher, indicating that Cu precipitates can form heterogeneous nucleation sites between the Fe2SiTi phase precipitates, promoting the synergistic strengthening effect on the steel.

[0054] The size of Cu precipitates in the S1 sample remains small after 12h of aging, indicating slow precipitation kinetics. This effect can be explained by the lack of Cu solubility in the co-sited Fe2SiTi, similar to Cu and M2C carbides. In addition, the difference in Cu size between S1 and S2 affects the strengthening effect on the material, which is related to the presence and absence of Nb aggregates in S1 and S2. Nb hinders the growth of Cu clusters because Nb inclusions on Cu clusters are thermodynamically unfavorable, which is related to the slow diffusion of Nb. Therefore, the size of Cu precipitates in the Nb-poor S2 sample is larger than that in the Nb-rich S1 sample, causing differences in strengthening effects.

[0055] Nb diffusion is a prerequisite for the formation of Cu clusters, but the diffusion rate is relatively slow, resulting in the aggregation of Nb in local areas, which further promotes the precipitation of Nb-rich Fe2SiTi phase. Nb diffuses forward from the Cu clusters, resulting in the co-precipitation of Fe2NbLaves phase. Therefore, the presence of Nb in Fe2SiTi causes the Fe2SiTi content in the S1 sample to be significantly higher than that in the S2 sample, where there is no Nb aggregation in the precipitation of the latter sample.

[0056] The precipitation kinetics of Fe2SiTi are closely related to Nb content, Si diffusion, and Cu precipitates, which play a fundamental role in the precipitation behavior of Fe2SiTiHeusler phase.

[0057] The price advantage of the present invention is:

[0058] The current S1 sample is competitive with other commercial HSLA phases in terms of hardness / unit mass price index. This invention confirms that the use of Fe2SiTi Heusler phase is a suitable strategy to promote the design of lighter, higher strength, lower cost marine HSLA.

[0059] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A process for preparing high-strength steel for ship hull structure, characterized in that: The following steps are involved: 1) Screening 100,000 combinations in the HSLA-115 combinatorial space, and using the selected research samples based on the ICM framework of CALPHAD thermodynamics, the Thermo-Calc software was used for high-throughput calculation to determine the sample composition. The specific composition by mass percentage is: 0.06% C, 88% Fe, 2.6% Al, 1.6% Si, 2.5% Ti, 0.8% Cr, 1% Mn, 0.6% Ni, 1.5% Cu, 0.54% Nb, 0.8% Mo; 2) Based on the sample composition obtained in step 1), a balance with an accuracy of ±0.1 mg is selected to weigh the elemental substance, and an arc melting furnace is used to cast the sample in a vacuum, argon-filled atmosphere and a water-cooled copper mold. The cast sample is repeatedly remelted to ensure uniform chemical composition, and pure Zr is used to remove the remaining O2 in the casting chamber; 3) homogenizing the sample obtained by casting in step 2) at 1190-1210° C. for 115-125 min, and then quenching with water; 4) The sample after homogenization treatment in step 3) is subjected to aging treatment at 490-510° C., and finally water quenched to room temperature to obtain high-strength steel for hull structure.

2. The preparation process according to claim 1, characterized in that: In the step 1), the Thermo-Calc software is used for high throughput computing application programming interface toolkit, i.e. TC-Python with TCFE9 steel database.

3. The preparation process according to claim 1, characterized in that: In the step 2), the purity of the single element is high purity > 99.9wt.%.

4. The preparation process according to claim 1, characterized in that: In the step 2), the cast sample is repeatedly remelted 5 to 7 times.

5. The preparation process according to claim 1, characterized in that: In the step 4), the aging treatment process is: heat preservation treatment is performed at a constant temperature of 500° C. for 2, 4, 8 and 12 hours respectively.

6. The preparation process according to claim 1, characterized in that: In step 4), TC-Prisma simulation is used to estimate the optimal range of failure time, and the main parameter is the interface free energy γ, wherein regarding the precipitation behavior of the Fe2SiTi phase in the Fe-Si-Ti system, the constant value γ is set to 0.145 J / m in the aging simulation. 2 .

7. The preparation process according to claim 1, characterized in that: In the step 4), the obtained high-strength steel for hull structure contains Heusler phase.

8. The preparation process according to claim 1, characterized in that: In the step 4), the obtained high-strength steel for hull structure has a tensile strength of 840-870 MPa, an elongation of 17.5-22.5%, and a total impact absorption energy of 45.3-65.3 J in a Charpy V-notch test at -40°C.

9. A high-strength steel for hull structure prepared by the preparation process according to any one of claims 1 to 8.

10. Use of the high-strength steel for hull structure according to claim 9 in ship steel.